To Align Multimodal Lumbar Spine Images via Bending Energy Constrained Normalized Mutual Information. - Wu, Shibin; He, Pin; Yu, Shaode; Zhou, Shoujun; Xia, Jun; Xie, Yaoqin (BioMed Research International, 2020)
To align multimodal images is important for information fusion, clinical diagnosis, treatment planning, and delivery, while few methods have been dedicated to matching computerized tomography (CT) and magnetic resonance (MR) images of lumbar spine. This study proposes a coarse-to-fine registration framework to address this issue. Firstly, a pair of CT-MR images are rigidly aligned for global positioning. Then, a bending energy term is penalized into the normalized mutual information for the local deformation of soft tissues. In the end, the framework is validated on 40 pairs of CT-MR images from our in-house collection and 15 image pairs from the SpineWeb database. Experimental results show high overlapping ratio (in-house collection, vertebrae 0.97 ± 0.02 , blood vessel 0.88 ± 0.07 ; SpineWeb, vertebrae 0.95 ± 0.03 , blood vessel 0.93 ± 0.10) and low target registration error (in-house collection, ≤ 2.00 ± 0.62 mm ; SpineWeb, ≤ 2.37 ± 0.76 mm) are achieved. The proposed framework concerns both the incompressibility of bone structures and the nonrigid deformation of soft tissues. It enables accurate CT-MR registration of lumbar spine images and facilitates image fusion, spine disease diagnosis, and interventional treatment delivery.